Scientometric Analysis as a Tool for Identifying Scientific Trends in the Region - A. R. Gatiyatov; M. R. Safiullin; A. A. Gataullina (Высшее образование в России, 2025)
The article is devoted to the identification of promising scientific subject areas of   the region on the basis of structural analysis of statistical information at the regional, national and worldwide levels. Such an approach will help to determine the trends formed in the national science   and in the world scientific community. The study is based on scientometric analysis in the context of subject areas, including the assessment of the dynamics and quality of publications. The article uses data from international and national databases to carry out scientometric analysis of scientific subject areas of the Republic of Tatarstan using the tools of cluster analysis, matrix modeling, dynamic and structural analysis of statistical information. The peculiarity of the approach is the collection   and processing of information at the level of individual subjects of the Russian Federation on the basis of systematization of statistics on particular scientific and educational institutions represented in statistical databases, as well as comparison of subject areas of international and domestic classifiers (All-Russian Classifier of Specialties in Higher Education and eLibrary subject rubricator, detailed by the State Rubricator of Scientific and Technical Information). The analysis allowed to identify   the scientific directions growing in the global arena and localized in the republic, which can form a pool of promising demanded scientific directions, among them: biotechnology (neurotechnology); immunology and microbiology; agriculture and forestry and biology; other sectors of the economy (interdisciplinary directions); literature, literary studies, oral folk art; religion, atheism; economic directions development of which depends on a number of factors (formed scientific policy, support programs of the region). In addition, the importance of attention to the scientific areas that are declining in activity on the regional level but growing in the country and the world (physics; electrical engineering (engineering technologies); materials science, etc.) is outlined.